2016
DOI: 10.1021/acs.joc.6b01756
|View full text |Cite
|
Sign up to set email alerts
|

Polyanils and Polyboranils: Synthesis, Optical Properties, and Aggregation-Induced Emission

Abstract: A first series of polyanils were synthesized by a simple condensation between either isomers of phenylenediamine derivatives or 1,3,5-benzenetriamine and 4-(diethylamino)salicylaldehyde, while a second series resulted from the condensation between 4,6-dihydroxyisophthalaldehyde or 2,5-dihydroxyterephthalaldehyde and differently substituted anilines. All these polyanils showed good chelating abilities toward trivalent boron fragments such as BF or BPh to yield the corresponding boranils. The optical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 72 publications
(45 reference statements)
1
35
0
Order By: Relevance
“…More recently, boron complexes based on a substituted anil scaffold (boranil) have emerged with the view to compensate for the lack of upscalability of BODIPY dyes . These derivatives have rapidly proven to be attractive fluorophores due to their straightforward synthesis, good stability and overall brightness in organic to protic media . They have notably served as biomarkers for the bovine serum albumine (BSA) protein, paving the way for their use in in vivo molecular imaging.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…More recently, boron complexes based on a substituted anil scaffold (boranil) have emerged with the view to compensate for the lack of upscalability of BODIPY dyes . These derivatives have rapidly proven to be attractive fluorophores due to their straightforward synthesis, good stability and overall brightness in organic to protic media . They have notably served as biomarkers for the bovine serum albumine (BSA) protein, paving the way for their use in in vivo molecular imaging.…”
Section: Figurementioning
confidence: 99%
“…[14] These derivatives have rapidly provent ob ea ttractive fluorophores due to their straightforward synthesis, good stability and overall brightness in organic to protic media. [15] They have notably served as biomarkersf or the bovine serum albumine (BSA) protein, [16] pavingt he way for their use in in vivo molecular imaging. The currentp rimaryd rawback of boranild yes lies in their fluorescence emission wavelength which has up to now been centred mainlyi nt he green region,l imiting their use for biological applications.…”
mentioning
confidence: 99%
“…By using the fluorescent quantum yield, the ability of receptor 1 to emit absorbed light energy is characterized. The results acquired in solvents of different polarity indicated that the photoinduced energy transfer (PET) process was speed up in polar solvents, which led to a moderate fluorescence quantum yield …”
Section: Resultsmentioning
confidence: 99%
“…The results acquired in solvents of different polarity indicated that the photoinduced energy transfer (PET) process was speed up in polar solvents, which led to a moderate fluorescence quantum yield. [35][36][37][38] The sensing ability of receptor [39,40] Under similar situations, receptor 1 did not shows any selectivity and sensitivity towards the tested anions ( Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Herein we report the synthesis of a Schiff base and a tetraphenyl hydroxy phenyl imidazole with an efficient ESIPT phenomenon resulting from strong hydrogen bonding and their boron complexes (boranil and borate respectively). In recent years, the coordination of a π‐conjugated chelate to a boron (III) fragment, as BF 2 has led to the development of alternative B (III) luminescent complexes which have been synthetized from saturated bidentate N‐N, O‐O chelates and N‐O . In this context, we have chosen to synthesize two compounds presenting the N‐O π system and their boron complexes where they have been characterized as promising fluorescent dyes with potential for biolabeling purposes and appropriate emitters for electroluminescent devices (Scheme and ).…”
Section: Introductionmentioning
confidence: 99%